2023
DOI: 10.1007/s11938-023-00420-6
|View full text |Cite
|
Sign up to set email alerts
|

Endobariatrics: a Still Underutilized Weight Loss Tool

Abstract: Purpose of review Bariatric and metabolic endoscopic therapies provide an option for patients seeking clinically significant weight loss with fewer adverse events than conventional bariatric surgery. Our aims are to provide an overview of the current state of primary endoscopic treatment options for weight loss and to emphasize the importance of including these therapies when presenting weight loss options to qualified patients. Recent findings Bariatric endoscopy proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Several retrospective studies and randomized clinical trials have demonstrated that BETs are associated with significant weight loss and an improvement of comorbidities caused by obesity [1 , 2] . Endoscopic sleeve gastroplasty (ESG) is a minimally invasive endoscopic procedure designed to treat grade 1 obesity [1] , [2] , [3] 4] ; it consists of an endoscopic suture of the anterior and posterior walls of the stomach along the greater curvature, resulting in a reduction of the gastric volume by 80%. This leads to a decreased food intake, with significant weight loss at 1-year follow-up [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies and randomized clinical trials have demonstrated that BETs are associated with significant weight loss and an improvement of comorbidities caused by obesity [1 , 2] . Endoscopic sleeve gastroplasty (ESG) is a minimally invasive endoscopic procedure designed to treat grade 1 obesity [1] , [2] , [3] 4] ; it consists of an endoscopic suture of the anterior and posterior walls of the stomach along the greater curvature, resulting in a reduction of the gastric volume by 80%. This leads to a decreased food intake, with significant weight loss at 1-year follow-up [5] .…”
Section: Introductionmentioning
confidence: 99%